Casimir force between eccentric cylinders - Dalvit, D.A.R. (2004)
We consider the Casimir interaction between a cylinder and a hollow cylinder, both conducting, with parallel axis and slightly different radii. The Casimir force, which vanishes in the coaxial situation, is evaluated for both small and large eccentricities using the proximity approximation. The cylindrical configuration offers various experimental advantages with respect to the parallel planes or the plane-sphere geometries, leading to favourable conditions for the search of extra-gravitational forces in the micrometer range and for the observation of finite-temperature corrections.